Bacteraemia of oral origin in children—A Systematic review and network meta‐analysis. (29th July 2021) - Charlotte Höfer, Karolin; Graf, Isabelle; Adams, Anne; Kuhr, Kathrin; Plum, Georg; Schwendicke, Falk; Brockmeier, Konrad; Johannes Noack, Michael
Abstract: Objectives: To systematically review the prevalence of bacteraemia, triggered by dental intervention and home oral hygiene practices, in children. The network meta‐analysis (NMA) quantitatively compared the risk of bacteraemia triggered by dental extractions and home and professional cleaning procedures. Materials and Methods: Clinical trials with the outcome "bacteraemia in children" were searched. The NMA was performed using the frequentist weighted least‐squares approach comparing the odds ratios (OR) of different interventions. Results: Among 11 of 13 studies, dental treatment was performed under general anaesthesia. In 2, 381 patients, bacteraemia occurred in 38.7%–56% patients following single‐tooth extractions, in 22%–46% after manual toothbrushing (MTB), and in 26%–78% after power toothbrushing (PTB). When MTB was set as the reference (OR 1), rubber cup polishing showed a slightly higher risk (OR 1.26) of bacteraemia. PTB presented a higher risk (OR 1.79–2.27) than with single‐tooth extractions (OR 1.55) but lower than that with multiple extractions (OR 2.55). Conclusion: Daily use of MTB and routine professional cleaning were associated with the lowest risk of developing bacteraemia in children with gingivitis, almost as much as with a single‐tooth extractions. Improved plaque control with PTB increased the risk of bacteraemia. There is limited evidence on gingivitis‐free and systemically‐diseased children.